Intensifikasi Pembelajaran Kontekstual Untuk Meningkatkan Prestasi Belajar dan Sikap Terhadap Bahasa Indonesia - Suroso Suroso (Jurnal Dewantara, 2019)
Active involvement of students physically and emotionally, it is likely that the learning process will give the impression of interesting and fun, even challenging. Emotional experiences provided have the opportunity to change students' attitudes towards Indonesian subjects. This research was conducted at 6 Metro Junior High School with a total of 26 students. The average learning achievement increased from 2.54 from Pre-Cycle to Cycle I, starting from 4.21 to 6.75. Then it increased by 1.08 from 6.78 to 7.83 in Cycle II. Thus there is an increase in learning achievement from Prasiklus, Cycle I, and Cycle II. This increase has exceeded the planned indicator achievement, which is 7.5.